Who initiates price competition when generic entrants are introduced into the South Korean pharmaceutical market? - Son, Kyung-Bok (Frontiers in Public Health, 2022)
Background Price competition has the potential to reduce health expenditures without hindering pharmaceutical innovation. However, empirical evidence on price competition after generic drugs are introduced is scarce. This study investigates product- and substance-level determinants of price competition following the entry of generics into the South Korean market. Methods We selected substances that were approved by the Ministry of Food and Drug Safety from 2000 to 2019, linked their corresponding pharmaceutical products, measured the degree of price competition under various scenarios, and utilized multilevel analysis to investigate the determinants of price competition. Results A total of 986 substances and 12,109 corresponding pharmaceutical products were identified. Only 11% of products were affected by price competition in the 10% scenario. However, the number increased to 43% when we measured price competition at the substance level. Major domestic manufacturers mainly initiated price competition at the product level, while foreign manufacturers were reluctant to initiate price competition. At the substance level, the maximum reimbursement price was a significant determinant of price competition. Conclusion Price competition at the product level is rare in South Korea. In contrast, the market is quite price competitive at the substance level. Policy options could be introduced to encourage “discounted generic” substitution in an effort to maximize the effects of price competition at the substance level. Major domestic manufacturers are essential in the introduction of discounted generics into the South Korean health system.